2018
DOI: 10.1001/jama.2018.10090
|View full text |Cite
|
Sign up to set email alerts
|

Glyburide vs Insulin for Gestational Diabetes—Reply

Abstract: Reasons for cigarillo initiation and cigarillo manipulation methods among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previous randomized clinical trials comparing glyburide and insulin for GDM treatment have been criticized for incorrect dosing of glyburide and for allowing greater flexibility of the insulin regimen than for the glyburide regimen. 41,42 In addition, almost all prior randomized trials had the primary outcome of maternal glycemia and were not powered to look at perinatal outcomes. 8 Although initially thought not to cross the placenta, it has been confirmed that glyburide does cross the placenta, and fetal glyburide concentrations decrease rapidly over the 24-hour period after glyburide intake.…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized clinical trials comparing glyburide and insulin for GDM treatment have been criticized for incorrect dosing of glyburide and for allowing greater flexibility of the insulin regimen than for the glyburide regimen. 41,42 In addition, almost all prior randomized trials had the primary outcome of maternal glycemia and were not powered to look at perinatal outcomes. 8 Although initially thought not to cross the placenta, it has been confirmed that glyburide does cross the placenta, and fetal glyburide concentrations decrease rapidly over the 24-hour period after glyburide intake.…”
Section: Discussionmentioning
confidence: 99%
“…3 9 13 14 15 The oral antidiabetic medications cross the placenta, and although current data demonstrate no adverse short-term effects on maternal or neonatal health from oral antidiabetic therapy during pregnancy, data on long-term outcomes are limited. 16 17 18 19 Furthermore, in two randomized control trials, oral antidiabetic medications failed to provide adequate glycemic control in 23 to 28% of women with GDM. 20 21…”
mentioning
confidence: 99%
“…A systematic review in 2015 suggested that glyburide was associated with a greater risk of infant macrosomia and neonatal hypoglycemia than insulin, and it failed to control maternal glucose adequately in approximately 25%, 6 although a subsequent Cochrane review found no clear difference between treatments. 7 In this issue of JAMA, Sénat and colleagues 8 for the Groupe de Recherche en Obstétrique et Gynécologie in France report the results of a multi-institutional randomized clinical trial designed to investigate whether gestational diabetes treatment with glyburide was not inferior to treatment with insulin with respect to prevention of perinatal complications. Noninferiority trials are based on the supposition that if the difference in effect between 2 treatments in rates of a particular outcome does not exceed a prespecified margin, then one treatment is not inferior to the other.…”
mentioning
confidence: 99%
“…The drug should optimally be given 1 hour before meals because its peak effect is at 3 to 4 hours after ingestion, with return to baseline at 8 hours, rendering it impractical as a bedtime dose to control fasting glucose levels. 9 In this trial, 8 glyburide was started at 2.5 mg once per day irrespective of fasting or postprandial hyperglycemia and could only be increased every 4 days. The maximum dosage of glyburide was 20 mg/d, and the mean dose received (from the start of therapy until delivery) was only 5.4 mg. No information was given on the timing of glyburide administration with respect to meals or how high the average patient's glyburide dose was titrated.…”
mentioning
confidence: 99%